Na2Si3O7/BaO composites for the gamma-ray shielding in medical applications: Experimental, MCNP5, and WinXCom studies - Caglar, Mustafa; Kayacik, Hande; Karabul, Yasar; Kilic, Mehmet; Ozdemir, Zeynep Guven; Icelli, Orhan (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
The role of BaO in the glassy structured Na2Si3O7 was investigated in the context of gamma radiations shielding parameters in the study. The mass attenuation coefficient, half layer value, and mean free path of the Na2Si3O7/BaO composites were calculated experimentally for the photons with the energies of 81 keV and 356 key emitted from 133Ba point radioactive source. The same parameters were also calculated by Monte Carlo N-particle simulation (MCNP5) for the gamma photons which are emitted from Ba-133, (241)AM (TC)-T-99m, (LU)-L-177, Ir-192, and Cs-137 radioactive sources. The effective atomic number and effective electron density were determined by WinXCom software. Additionally, the scattered gamma photon intensity of the composites was realized for the energy of 364 key and compared with the most utilized radiation shielding material lead. It was concluded that the composite having the highest BaO additive exhibits the best gamma photon absorption ability at all energies investigated.
Keywords: Sodium silicate; Barium oxide; Composite; Gamma-ray shielding; MCNP; WinXCom; EFFECTIVE ATOMIC NUMBERS; X-RAY; ATTENUATION COEFFICIENTS; ELECTRON-DENSITIES; GLASSES; PARAMETERS; PROGRAM; LEAD; Nuclear Science & Technology